Structural health monitoring of building columns using long gauge FBG sensors - Chua, Joo Han (Nanyang Technological University, 2021)
Structural Health Monitoring (SHM) is essential to provide valuable information on civil and building structural conditions. Currently, widely used sensors are ‘point’ sensors which do not reflect the overall condition of a structure. A long gauge sensor that provides global monitoring with accurate feedback throughout a structure would be useful in SHM. In this report, a long gauge sensor is developed with uniform and chirped FBG sensor. The design methodology and process are explained and discussed. The chirped FBG long gauge sensor is then examined and assessed through a compression test while embedded inside a column. Strain gauge readings are used to compare the result of this sensor. Based on the results, the chirped FBG long gauge sensor offers greater prospects in structural monitoring. The analysis and discussion of uniform FBG long gauge sensor will be included in the part 1 of this project, ST-39AB-1.